A STUDY ON DIFFERENT BETWEEN MODERN BANKS AND TRADITIONAL BANKS SERVICES - S. Suguna; R. Nagalakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The primary objective of this study is to explore the factors driving the adoption of electronic banking and its relationship with traditional banking services. Focusing on the retail sector of the financial industry in Indore city, the research aims to investigate the influence of firm-specific and non-specific characteristics (such as technology, market, and environment) on the decision-making process of banks in adopting new technical platforms for online banking transactions. By analyzing these factors, the study seeks to provide a comprehensive understanding of how electronic banking complements or substitutes traditional banking services. Ultimately, the goal is to contribute to spreading technology in the banking sector by shedding light on the dynamics between electronic and traditional banking distribution channels.